Study on the Presence of the Rhinoceros Hornbill (Buceros Rhinoceros) and its Food Potential in the Pondok Buluh Forest Training Center - Rozalina; Sarintan E. Damanik; Tri Adimas Sanjaya (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the presence of rhinoceros hornbills and their potential food trees in the Pondok Buluh Training Forest (KHDTK). Data collection on the presence of hornbill species was carried out using a concentrated point method determined by field observations. Observations were conducted at six observation locations along the rhinoceros hornbill's daily movement path. Observations were conducted at time intervals between 07.00-09.00 WIB (morning), 11.00-13.00 WIB (afternoon) and 15.00-17.00 WIB (evening), where these times are when rhinoceros hornbills are actively foraging and resting, so the opportunity for observation is greater. The data collected were encounter time, number of individuals, type of encounter (visual/audio) and encounter location. Data collection for potential food trees was carried out using the Species Area Curve Method with vegetation analysis. The parameters measured were species name (local and scientific), number of individuals, tree diameter at breast height and tree height. The vegetation analysis method used was the Species Area Curve Method. Based on the observation results, encounters with Rhinoceros Hornbills occurred at six observation points, namely at observation point 1 (coordinates N 02°46’45.3” and E 098°59’55.3”), observation point 2 (coordinates N 02°46’40.1” and E 099°00’02.3”), observation point 3 (coordinates N 02°46’80.2” and E 098°59’93.6”), observation point 4 (coordinates N 02°46’07.7” and E 098°59’06.6”), observation point 5 (coordinates N 02°46’24.768” and E 098°58’00.426”) and observation point 6 (coordinates N 02°46’24.456” and E 098°58’13.368”). The potential for food trees in the Pondok Buluh Training Forest KHDTK has a “good” regeneration rate so that it can support the survival of the rhinoceros hornbill.